Combining Circular and Gauss-Markov Mobility Models for FANET Enhancement - Abdulhameed, Alyaa Safaa; Behadili, Suhad Faisal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Nowadays, the effectiveness of Flying Ad-hoc Networks (FANETs) has proven their importance in many fields, such as the military, healthcare, entertainment, etc. In such networks, realistic mobility modeling is pivotal for accurately simulating Unmanned Aerial Vehicle (UAV) behaviors and their interactions within the network. To achieve this realism and improve network performance metrics of the network, multiple Mobility Models (MMs) can be integrated, allowing UAVs to exhibit complex movement patterns that reflect real-world dynamics. This paper proposes a combination of Circular Mobility (CM) and Gauss-Markov (GM) models (CCGM) in a superposition mobility model to determine the final pattern of the model and how it affects the Quality of Services (QoS). So, the OMNeT++ was used as a simulation tool to achieve this purpose. The QoS used for analyzing the model are End-to-End Delay (E2ED), throughput, Packet Delivery Ratio (PDR), jitter, and packet loss. The simulation results were introduced and compared with respect to four scenarios. The first two scenarios implied the models independently, while the last two scenarios implied the proposed model (CCGM); each scenario was evaluated with Ad-hoc On Demand Distance Vector (AODV), Destination Sequenced Distance Vector (DSDV), and Greedy Perimeter Stateless Routing (GPSR) routing protocols. The simulation results demonstrate that the proposed model (CCGM) outperforms the GM and CM models in terms of E2ED, PDR, throughput, jitter, and packet loss. Consequently, the CCGM model exhibits an average E2ED of best results with a GPSR of 0.009 seconds in scenario 4, while it exhibits the best results in AODV with PDR of 90.82%, throughput of 669614, jitter of 0.021, and packet loss of 9.18% in scenario 4 as well. This indicates that the CCGM model could enhance the QoS and movement realism, making it useful in FANET applications